2020
DOI: 10.3390/biom10050688
|View full text |Cite
|
Sign up to set email alerts
|

Functional Implications of Cathelicidin Antimicrobial Protein in Breast Cancer and Tumor-Associated Macrophage Microenvironment

Abstract: It is well-established that tumor-associated macrophages (TAMs) play an important role in breast cancer development. Accumulating evidence suggested that human cathelicidin antimicrobial protein (CAMP), which is mainly expressed in host defense cells such as macrophages, is crucial not only in combating microorganisms but also promoting tumor growth. Here we report the interaction of CAMP with TAMs in breast cancer. CAMP expression was upregulated in cancer tissues and in the circulation of breast cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
(74 reference statements)
0
13
0
1
Order By: Relevance
“…Paradoxically, LL-37 promotes tumorigenesis in breast cancer, ovarian cancer, malignant melanoma, lung cancer, prostate cancer, pancreatic cancer and squamous cell carcinoma of the skin [ 256 ]. For instance, LL-37 was found to be highly expressed in breast cancer [ 257 ], and promoted the migration and metastasis of breast cancer cells [ 258 ]. In ovarian cancer, it enhances the proliferation, migration and invasion of ovarian cancer cells [ 247 ].…”
Section: Activity Of Ampsmentioning
confidence: 99%
“…Paradoxically, LL-37 promotes tumorigenesis in breast cancer, ovarian cancer, malignant melanoma, lung cancer, prostate cancer, pancreatic cancer and squamous cell carcinoma of the skin [ 256 ]. For instance, LL-37 was found to be highly expressed in breast cancer [ 257 ], and promoted the migration and metastasis of breast cancer cells [ 258 ]. In ovarian cancer, it enhances the proliferation, migration and invasion of ovarian cancer cells [ 247 ].…”
Section: Activity Of Ampsmentioning
confidence: 99%
“…В случае рака молочной железы было показано, что уровень Hp повышен не только в крови, но и в опухолевых тканях. Причём неожиданно оказалось существование функциональной связи между Hp и гликолитическими ферментами, такими как глюкозо-6-фосфатизомераза и гексокиназа [96].…”
Section: гаптоглобин и его протеоформы как потенциальные биомаркеры заболеванийunclassified
“…In the case of breast cancer, it has been shown that the level of Hp is increased not only in the blood but also in tumor tissues. Moreover, it was unexpectedly found that there is a functional relationship between Hp and glycolytic enzymes, such as glucose-6-phosphate isomerase and hexokinase [ 96 ]. Another disease recently found to have elevated plasma Hp levels is acute myocardial infarction in young adults [ 97 ].…”
Section: Haptoglobin and Its Proteoforms As Potential Biomarkers Of Diseasesmentioning
confidence: 99%